LONGITUDINAL AND LATERAL DYNAMIC OF COMMERCIAL VEHICLE WITH 6x6 DRIVE (Perner's Contacts, 2015)
The paper deals with the description of computational models of commercial vehicle and its lateral and longitudinal dynamic. This model uses own blocks which they are created using the basic elements of software Simulink. The article mainly describes the function of block of dynamic vehicle and one demonstrates the assembly of commercial vehicle with 6x6 drive. In conclusion, a simulation of driving manoeuvres is done to verify the functionality of the assembled commercial vehicle model.
Keywords: Simulink, Commercial Vehicle, Longitudinal and Lateral Dynamic, Library, Tyre